Challenging factors among homeowners on solar panel utilization for residential building in Seri Iskandar, Perak / Nor Amirul Hakim Mohamad and Mohd Nurfaisal Baharuddin - Mohamad, Nor Amirul Hakim; Baharuddin, Mohd Nurfaisal (2023)
Energy consumption in this world has significantly increased in recent years as a result of the population growth, industrialization, and development of emerging economies. Solar power only meets a low percentage of the world's energy demands especially for residential buildings. Hence, this study was conducted to change the perception and improve the thoughts of homeowners regarding solar panel utilization for residential building with the main objectives of to identitify the challenging factors among homeowners on solar panel utilization for residential buildings, then to suggest the most challenging factors among homeowners on solar panel utilization for residential buildings. This research involved both qualitative and quantitative method. Virtual interview session been carried out to selected experts that have closely related to the field scope of this study. Meanwhile, quantitative methods were used where questionnaires distribution to the homeowners of selected case study have been done and the collected data was analyzed using the Statistical Package for the Social Science (SPSS) software. The overall findings of this research indicated the most challenging factors that influence solar panel utilization among homewoners for residential building are financial or cost barriers, lack of awareness and knowledge, and lack of government incentives. In order to change the perception of homeowners regarding solar panel utilization for residential building, several recommendations are being provided to solve the problem for the purpose of further research.